Strategic Review: Implications of Proposals to Date for Mitigation Contributions - Moarif, Sara (OECD Publishing, 2015)
Parties to the UN Framework Convention on Climate Change (UNFCCC) produced a negotiating text in February 2015, which forms the basis for negotiations toward a climate change agreement scheduled for adoption at the 21st Conference of the Parties in December 2015. This document aims to better understand proposals in the Geneva negotiating text related to the notion of strengthening nationally determined contributions (NDCs) over time, contained under the headings "strategic review of implementation", "aggregate ambition assessment" and "enhanced ambition mechanism". This paper focuses on how key elements of these proposals might apply to mitigation contributions or the mitigation component of NDCs: The document examines the main proposals in terms of their relevance, coherence, assumptions, scope, and feasibility, in the context of a cycle of mitigation contributions that seek to become more ambitious over time. It also explores whether the proposals are likely to be effective in achieving their foreseen outcomes, the majority of which involve changes to NDCs. In general, it finds that there is significant overlap between proposals for various "review" processes in different parts of the Geneva negotiating text, as well as overlap with monitoring, reporting and verification processes under the UNFCCC. The document also presents some broad messages on the subject of "strategic review" expressed during the CCXG Global Forum in March 2015. It is currently unclear what a review or assessment process would comprise, largely because it relates to an overarching process - a cycle of contributions - for which there is not yet an agreed vision or scope
Keywords: Energy; Environment